Edited by Katsuhiko Ariga, Masakazu Aono (Amsterdam, 2017)
Supra-materials Nanoarchitectonics provides the latest information on design at the nanoscale, presenting a range of the new challenges that arise as the manipulation techniques that work at the macro- and micro-scale do not work at the nanoscale. The term nanoarchitectonics, coined by Japan's National Institute for Materials Science (NIMS), describes the organized interactions required at the nanoscale, replacing the traditional structure-building approach used in materials design.
Keywords: Vật liệu kết cấu Nano,Nanostructured materials